ChemInform Abstract: Cs3W3PO13: A Tungsten Phosphate with One‐Dimensional Zigzag Tunnels Exhibiting Strongly Anisotropic Thermal Expansion. Issue 33 (27th July 2016) - Gong, Pifu; Jiang, Xingxing; Yang, Yi; Luo, Siyang; Huang, Rongjin; Li, Laifeng; Chen, Chuangtian; Lin, Zheshuai
Abstract: Single crystals of the title compound are prepared from a mixture of CsCO3, WO3, NH4 H2 PO4, and B2 O3 in the molar ratio of 4:3:3:3 using B2 O3 and WO3 as a flux (Pt crucible, 973 K, 24 h).